Cytotoxicity evaluation using cryopreserved primary human hepatocytes in various culture formats. (6th September 2016) - Richert, Lysiane; Baze, Audrey; Parmentier, Céline; Gerets, Helga H.J.; Sison-Young, Rowena; Dorau, Martina; Lovatt, Cerys; Czich, Andreas; Goldring, Christopher; Park, B. Kevin; Juhila, Satu; Foster, Alison J.; et al.
Abstract: Sixteen training compounds selected in the IMI MIP-DILI consortium, 12 drug-induced liver injury (DILI) positive compounds and 4 non-DILI compounds, were assessed in cryopreserved primary human hepatocytes. When a ten-fold safety margin threshold was applied, the non-DILI-compounds were correctly identified 2 h following a single exposure to pooled human hepatocytes (n = 13 donors) in suspension and 14-days following repeat dose exposure (3 treatments) to an established 3D-microtissue co-culture (3D-MT co-culture, n = 1 donor) consisting of human hepatocytes co-cultured with non-parenchymal cells (NPC). In contrast, only 5/12 DILI-compounds were correctly identified 2 h following a single exposure to pooled human hepatocytes in suspension. Exposure of the 2D-sandwich culture human hepatocyte monocultures (2D-sw) for 3 days resulted in the correct identification of 11/12 DILI-positive compounds, whereas exposure of the human 3D-MT co-cultures for 14 days resulted in identification of 9/12 DILI-compounds; in addition to ximelagatran (also not identified by 2D-sw monocultures, Sison-Young et al., 2016 ), the 3D-MT co-cultures failed to detect amiodarone and bosentan. The sensitivity of the 2D human hepatocytes co-cultured with NPC to ximelagatran was increased in the presence of lipopolysaccharide (LPS), but only at high concentrations, therefore preventing its classification as a DILI positive compound. In conclusion (1) despite suspension human hepatocytes having the greatest metabolic capacity in the short term, they are the least predictive of clinical DILI across the MIP-DILI test compounds, (2) longer exposure periods than 72 h of human hepatocytes do not allow to increase DILI-prediction rate, (3) co-cultures of human hepatocytes with NPC, in the presence of LPS during the 72 h exposure period allow the assessment of innate immune system involvement of a given drug.